2017
DOI: 10.1007/s40846-017-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collagen-Polycaprolactone Nanofibers Matrix Coating on the In Vitro Cytocompatibility and In Vivo Bone Responses of Titanium

Abstract: The objective of this study was to improve the biomechanical performance of titanium (Ti) using a biocompatible electrospun nanofiber matrix. The study is based on the hypothesis that coating a Ti surface with a nanofiber matrix (NFM) made of collagen (CG) and polycaprolactone (PCL) electrospun nanofibers could increase the mechanical fixation of Ti/bone by improving the surface and cytocompatibility properties of Ti. This study prepared Ti samples with and without CG-PCL NFM coatings. This study determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, there is the need of exploring the efficacy and widening reliable models for screening the most promising materials before the adoption of in vivo models and in clinical use. Several in vivo models are used to test osseointegration of an implant [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is the need of exploring the efficacy and widening reliable models for screening the most promising materials before the adoption of in vivo models and in clinical use. Several in vivo models are used to test osseointegration of an implant [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Among biological matrix, type I collagen (COLL I) plays a role in cell metabolism and physiology because it is the major structural protein of bone matrix and it is able to induce OB function, adhesion, differentiation and bone ECM component secretion [37,38]. In literature, COLL I (obtained from calf skin or rat tail) is already used as biological coating material of a Ti-6Al-4V alloy implant, showing high in vitro MSC attachment, spreading, proliferation and differentiation, OB response [4,[38][39][40][41] and in vivo high bone-to-implant contact (BIC or osseointegration) and bone ingrowth [4,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we etched microgrooves in metal implants using a precision diamond sawing machine [10]. Our preliminary studies showed that microgrooving cementless titanium (Ti) implants significantly improve biocompatibility, mechanical stability, and osseointegration of the device [11,12]. Laser-induced micro-and nanotexturing that increase the surface area and roughness may further enhance the stability of press-fit implants by increasing friction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Grooves on implants induce a higher amount of osteoblast cell function [ 14 ] and implant–bone contact area [ 15 ] compared to implants without grooves. Another way to improve the osseointegration of an implant is to coat the implant with a functional biomaterial coating that creates an extracellular matrix on the implant [ 16 ]. An extracellular matrix provides the principal means by which mechanical information is communicated between tissue and cellular levels of function [ 17 ].…”
Section: Introductionmentioning
confidence: 99%